Pembuatan Aplikasi Salesforce Automation System pada Toko IV Berbasis Android - Soen, Surya Soenaryo; Yulia Yulia; Henry Novianus Palit (Jurnal Infra, 2017)
Currently, the information system that was recently implemented in IV shop worked well in the long term for administration purpose. Meanwhile, IV shop still lacks any supporting application for their front-end sales department, which has direct contact with customer in daily basis.The fact that IV shop sells various car-related products with various brands troubles their salespeople because they have to learn and understand each product’s uniqueness. In addition, occasionally, there are communication problems between manager and salespeople. The salespeople may not fully understand the current promotion in IV shop. Furthermore, there were some occasions that they forgot their assigned tasks.In order to solve the current condition, an android application were developed. This Android application was created by using Ionic Framework, AngularJS, Google Firebase database, Amazon RDS database, and SQLite database. This application has 7 major functions, which are: Account Management, Incentive Management, Company Timeline, Leads Management, Opportunity Management and Company Statistics. There are some additional functions to support the front-end salespeople and manager, such as: user tracking, private-chatting, group-chatting, and real-time information for data-driven decision.The final result of this application development lets users get a better insight about products and know the recent important information faster and more effective. This application also works well with the existing system.